Children rights to maintenance under Islamic and civil law in Malaysia: towards harmonisation of laws - Hj Ibrahim, Badruddin; Mohd, Azizah; A. Kadir, Nadhilah (2023)
Islamic law regards children as a trust (Amanah) from Allah s.w.t. A trust that is to be discharged by parents through performance of certain responsibilities which include provision of care and custody, guardianship, and maintenance. Islamic law imposes the duty to maintain children primarily on the father. While relatives and the mother will also shoulder the responsibilities whenever the father is dead or is incapable of maintaining due to certain reasons like disabilities and poverty. It seems that Civil law to a certain extent, shares quite the same principle. This paper, therefore, deals with children rights to maintenance under two jurisdictions namely the Islamic and Civil law. Examination will focus on provisions of children rights to maintenance under both jurisdictions, the extent of this responsibility as well as the analysis on the idea of harmonisation of laws under Islamic law in Malaysia namely Islamic Family Law (Federal Territories) Act 1984) and Civil law on maintenance particularly the Law Reforms (Marriage and Divorce) Act 1976 and the Married. Women and Children Maintenance Acy 1950. The research will adopt qualitative research where the data and materials will be collected mainly from the library. Finally, the paper will propose certain recommendations for improvement of the laws wherever relevant and necessary.